Relationship between follicle size and ultrasound-guided transvaginal oocyte recovery - Seneda, M. M.; Esper, C. R.; Garcia, J. M.; de Oliveira, J. A.; Vantini, R. (Elsevier B.V., 2001)
We evaluated the relationship between follicle size and oocyte recovery (OR) using ultrasound-guided follicle aspiration. Thirty Holstein cows were subjected to OR without gonadotrophic therapy. Oocytes were recovered two to four times from each cow in a total of 67 aspiration sessions, Ovarian follicles with diameters less than or equal to4 mm and >4 mm were aspirated in separated groups. Recovered oocytes from each group were kept separate and submitted to in vitro maturation, fertilization, and culture to the blastocyst stage. A total of 430 follicles were aspirated, of which 154 (35.8%) were from follicles >4 mm and 276 (64.2%) were from follicles less than or equal to4 mm. Seventy-seven oocytes (50%) were recovered from follicles >4 mm and 200 (72.2%) were from follicles less than or equal to4 mm. Nineteen blastocysts were obtained from follicles >4 mm, whereas 45 blastocysts were obtained from follicles less than or equal to4 mm. Recovery rate was greater (P < 0.01) in follicles less than or equal to4 mm, Oocyte quality, cleavage rate and blastocyst development did not differ between different follicle sizes. Routine aspiration of small follicles (less than or equal to4 mm) could increase the number of oocytes available for in vitro development. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: follicle; oocyte recovery; oocyte maturation; embryonic development